176k views
4 votes
Work out the height of the following triangles

Work out the height of the following triangles-example-1
User Hbaromega
by
4.8k points

2 Answers

2 votes

A) height =
11.3cm .

B) height =
15.48cm .

Explanation:

Here , We need to calculate height of triangles let's do this :

A)

We draw a perpendicular from vertex to base line (8 cm ) , so length becomes 4 cm of base of triangle .

By Pythagoras Theorem we have ,


Hypotenuse^2 = Perpendicular^2+Base^2


Hypotenuse^2 = Perpendicular^2+Base^2


12^2 = Perpendicular^2+4^2


144 = Perpendicular^2+16


Perpendicular^2= 144-16


Perpendicular= √(128)


Perpendicular= √(2^6(2))


Perpendicular= 2^3√(2)


Perpendicular= 8√(2)cm

Therefore , height =
11.3cm .

B)

We draw a perpendicular from vertex to base line (14 cm ) , so length becomes 7 cm of base of triangle .

By Pythagoras Theorem we have ,


Hypotenuse^2 = Perpendicular^2+Base^2


Hypotenuse^2 = Perpendicular^2+Base^2


17^2 = Perpendicular^2+7^2


289= Perpendicular^2+49


Perpendicular^2=289-49


Perpendicular= √(240)


Perpendicular= 4√(15)cm

Therefore , height =
15.48cm .

User Foobarometer
by
5.4k points
6 votes

The height of first (a) triangle is 11.31 cm and the height of the second (b) triangle is 15.49 cm.

Explanation:

The given is,

Triangle (a) and (b)

Step:1

For first (a) triangle

(Ref the attachment (a))

b = 4 cm

hyp = 12 cm

From Pythagoras theorem,


Hyp^(2) = b^(2) +h^(2)...........................(1)

Equation becomes,


12^(2) =
4^(2) +
h^(2)

144 = 16 +
h^(2)

h =
√(128)

h = 11.314 cm

Step:2

For first (b) triangle

(Ref the attachment (b))

b = 7 cm

hyp = 17 cm

From Pythagoras theorem,


Hyp^(2) = b^(2) +h^(2)...........................(1)

Equation becomes,


17^(2) =
7^(2) +
h^(2)

289 = 49 +
h^(2)

h =
√(240)

h = 15.492 cm

Result:

The height of first (a) triangle is 11.314 cm and the height of the second (b) triangle is 15.492 cm.

Work out the height of the following triangles-example-1
User Akhilesh Pandey
by
4.8k points